PREDATORY PRICING, PRICE PENETRATION AND MARKET DISTORTION ACCORDING TO ISLAMIC ECONOMICS - Maulana, Irwan; Shima, Putri (STAI Asy-Syukriyyah, 2024)
In the short term, predatory pricing is very beneficial to consumers, but after removing competitors from the market and hindering potential new competitors, the dominant business actors or incumbent business actors hope to increase prices significantly. In marketing campaigns, pricing has an important role, with unfair pricing causing distortions in the global market. So that the sharia maqasyid is not achieved optimally as ordered by the Qur'an. Based on the discussion above, several conclusions can be made. Predatory pricing is considered an unfair trade practice, although there are some countries that do not prohibit it, this gives rise to various other conflicts such as price penetration and market distortion. The solution must be adjusted to the origin of the cause. If the cause is a change in genuine demand and genuine supply, then the control stage is carried out through market intervention. Meanwhile, when caused by distortion of genuine demand and genuine supply, the control mechanism is carried out through distortion removal, including the determination of price intervention to return the price to the state before the distortion.